Innovative Therapies for Acquired Hemophilia A - Franchini, Massimo; Focosi, Daniele (Seminars in Thrombosis and Hemostasis, 2024)
Acquired hemophilia A (AHA) is a rare autoimmune bleeding disorder which can be life-threatening. AHA is due to autoantibodies against coagulation factor VIII. Disease onset may be idiopathic (approximately half of the cases) or triggered by autoimmune disorders, cancers, drugs, infections, or pregnancy. Besides treating the underlying disorder, specific AHA treatments include management of bleeding and inhibitor eradication. Various first-line and second-line hemostatic and immunosuppressive agents are currently available for the management of AHA. Recently, the hemostatic drug emicizumab and the immunosuppressive drug rituximab have been the object of intense research from investigators as innovative promising therapies for AHA. This narrative review will be focused on the current status of the clinical use of these two off-label therapeutic agents in AHA.
Keywords: acquired hemophilia A; bleeding; rituximab; emicizumab